Starvation induces shrinkage of the bacterial cytoplasm - Handuo Shi; Corey S. Westfall; Jesse Kao; Pascal D. Odermatt; Sarah E. Anderson; Spencer Cesar; Montana L. Sievert; Jeremy Moore; Carlos G. Gonzalez; Lichao Zhang; Joshua E. Elias; Fred Chang; et al. (2021)
Significance Bacterial cells constantly face nutrient fluctuations in their natural environments. While previous studies have identified gene expression changes upon nutrient depletion, much less well known is how cellular morphology and cytoplasmic properties respond to shifts in nutrient availability. Here, we discovered that rapid switching of fast-growing Escherichia coli cells to nutrient-free conditions results in substantial shrinkage of the inner membrane away from the cell wall, especially at the new pole. Shrinkage was primarily driven by loss of cytoplasmic water content. Shrinkage was also exhibited by cells naturally entering stationary phase, highlighting its biological relevance across starvation conditions. The membrane-spanning Tol-Pal system was critical for robust entry into and recovery from shrinkage, indicating the importance of cell envelope homeostasis.